Choosing an Instant Messaging App: Security or Convenience? Comparison between Whatsapp and Telegram - Azzhan Shahrul; Aji Prasetya Wibawa (Universitas Ahmad Dahlan, 2021)
An increase in Instant Messenger (IM) application users makes it easier for people to get connected through social media. Application developers regularly offer updates. However, those updates don’t always satisfy users expectations, instead confuse them. Even users are sometimes hesitant to update the app thus they switch to another messaging platform. This research discusses the analysis and comparison of two IM applications that reached 100 million downloads on Play Store; Whatsapp and Telegram. The analysis process is carried out from the features use in the Instant Messenger application. The data collection procedure are conducted by viewing the traffic. The data acquisition technique is done by using literacy and observation study methods to get full access to smartphones. The results of the analysis are in the form of a comparing table between both IM applications and expected to be future reference for further reseach.Peningkatan pengguna aplikasi Instant Messenger (IM) memudahkan masyarakat untuk terhubung melalui media sosial. Pengembang aplikasi secara teratur menawarkan pembaruan. Namun, pembaruan tersebut tidak selalu memenuhi harapan pengguna, malah membingungkan mereka. Bahkan pengguna terkadang ragu untuk memperbarui aplikasi sehingga mereka beralih ke platform perpesanan lain. Penelitian ini membahas tentang analisis dan perbandingan dua aplikasi IM yang mencapai 100 juta unduhan di Play Store; Whatsapp dan Telegram. Proses analisis dilakukan dari fitur-fitur yang digunakan pada aplikasi Instant Messenger. Prosedur pengumpulan data dilakukan dengan melihat lalu lintas. Teknik akuisisi data dilakukan dengan menggunakan metode studi literasi dan observasi untuk mendapatkan akses penuh ke smartphone. Hasil analisis berupa tabel perbandingan antara kedua aplikasi IM dan diharapkan dapat menjadi acuan untuk penelitian selanjutnya.